SISTEM PENUNJANG KEPUTUSAN PEMILIHAN KEGIATAN PENERIMA BANTUAN SOSIAL DENGAN METODE SMART - Bayu Rahadi Mukti (CV. Multi Kreasi Media, 2024)
Social Assistance activity program is the provision of assistance in the form of money or goods from the central / local government addressed to individuals, families, groups or communities that are not continuous and selective in nature that aims to protect against the possibility of social inequality. However, the classic problem that often occurs in the field when distributing this aid is the inaccuracy of data on recipients of social assistance packages, as a result many people who should get social assistance do not get it and vice versa. In order for the distribution of this aid to be more accurate in accordance with the data of prospective recipients, a system was created that is able to assist related parties in making more accurate and targeted decisions. This decision making is based on community data processed using the SMART (Simple Multi-AttributeRating Technique) method.